2008
DOI: 10.1002/ajhb.20729
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements of Australian Aboriginal adults living in remote areas: Comparison with nationally representative findings

Abstract: To compare body size measurements in Australian Aboriginals living in three remote communities in the Northern Territory of Australia with those of the general Australian population. Height, weight, waist and hip circumferences and derivative values of body mass index (BMI), waist-hip ratio (WHR), waist-height ratio (WHT), and waist-weight ratios (WWT) of adult Aboriginal volunteers (n = 814), aged 25 to 74 years were compared with participants in the nationally representative 'AusDiab' survey (n = 10,434). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Indeed, young, healthy Indigenous adults are reported to have 30% less nephrons than non-Indigenous comparators as well as having a mean kidney volume that is 27% greater [9]. From an anthropometric perspective, the Australian Indigenous have a lower body mass, higher central fat and slimmer limbs [10]. Furthermore, they were shown to have a similar allele frequency to South Asians for some cytochrome P450 enzymes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, young, healthy Indigenous adults are reported to have 30% less nephrons than non-Indigenous comparators as well as having a mean kidney volume that is 27% greater [9]. From an anthropometric perspective, the Australian Indigenous have a lower body mass, higher central fat and slimmer limbs [10]. Furthermore, they were shown to have a similar allele frequency to South Asians for some cytochrome P450 enzymes [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, different ethnic groups have different body fat distributions [1-3]. Aboriginal women tend to have larger waist circumferences (WC), waist-to-hip ratios (WHR) and waist-to-height ratios (WHtR) compared to non-Aboriginal Australians [4]. Other anthropometric measurements than BMI can also be important in epidemiologic studies undertaken in Aboriginal people [5-7] due to their unique body shapes, with long-legs in proportion to their body height and low sitting height [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that Aboriginal body habitus profiles differ from AusDiab profiles (6). In addition, the current study demonstrates that the risk for diabetes in both sexes relative to the AusDiab participants is excessive at all levels of body size, including levels that are normal or low.…”
Section: Research Design and Methods -People From Four Remotementioning
confidence: 67%
“…Body size was measured by standard procedures, with few differences (6). In the AusDiab study, waist and hip circumferences were measured twice, and if they varied more than 2 cm, a third measurement was taken and the mean of the two closest measurements derived.…”
Section: Research Design and Methods -People From Four Remotementioning
confidence: 99%